Place Identity of Urban Heritage in Medan City (Case Study of Medan Post Office) - Baitha Ariyanti; Yenny Novianti; Sisca Olivia (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The concept of place identity examines the relationship between personal identity and physical location, emphasizing the importance of location in the lives of people and the communities that inhabit them. In the last twenty years, place identity has become an important issue in urban planning and design, especially in conservation or preservation. This research aims to identify the place identity of the Medan Post Office as one of the urban heritage in Medan City to maintain the historic building sustainably. Medan Post Office was chosen because it is located in the city center which is the center of accessibility with the area with the highest concentration of pedestrians and tourists so it is referred to as Medan’s Zero Point. This research used descriptive qualitative and quantitative methods. This research combines qualitative and quantitative methods through direct observation and interviews as well as conducting questionnaires to obtain information on respondents’ characteristics and perceptions of place identity variables. The results showed that the place identity formed in Medan Post Office as an effort to maintain urban heritage is supported by self-efficacy and self-esteem variables as the strongest identities. In contrast, continuity and distinctiveness variables are the weakest identities. The self-efficacy variable becomes the strongest identity due to the accessibility indicator at Medan Post Office, followed by self-esteem with high evaluation value. However, the continuity variable that reflects the value of the place still needs to be improved because its value is the lowest. So it needs further development to increase the continuity or distinctiveness of the place following its potential as urban heritage. Keywords: Place identity, urban heritage, Medan Pos Office, Medan City